Severe encephalopathy with brain atrophy and hypomyelination due to adenylosuccinate lyase deficiency - MRI, clinical, biochemical and neuropathological findings of Polish patients - Mierzewska, Hanna; Schmidt-Sidor, Bogna; Jurkiewicz, Elżbieta; Bogdańska, Anna; Kuśmierska, Katarzyna; Stępień, Tomasz (Folia Neuropathologica, 2009)
Adenylosuccinate lyase (ADSL) deficiency is an autosomal recessive disorder caused by mutation in the ADSL gene. The disease was identified in 1984 by Jaeken and van der Berghe as the first inborn defect of purine biosynthesis. Affected children revealed encephalopathy with epilepsy and marked psychomotor retardation. A neurological examination showed hypotonia, followed sometimes after years by spasticity. The diagnosis is based on detection in the urine and CSF succinyladenosine (S-Ado) and succinylaminoimidazole carboxamide ribotide (SAICAr). We present brain MR examinations of seven patients with ADSL deficiency in the correlation with their clinical findings. In all cases lack of myelination or of delayed myelination of cerebral white matter was seen. Additionally cerebral and cerebellar atrophy was observed. Neuropathological findings revealed damage of all cellular elements of brain tissue and are cause of observed MR changes. Hypo/dysmyelination seemed to be secondary to damage of oligodendroglia and axons of damaged neuronal cells.